Peningkatan Efisiensi Kinerja Apotek Menggunakan SIMRS Bridging dengan Sistem Apotek Online BPJS di RSKB Ropanasuri Padang - Junaidi, Ahmad (Universitas Labuhanbatu, 2025)
The use of Information Technology can help hospitals improve the quality of patient care and control drug bills to BPJS. RSKB Ropanasuri is a specialized surgical hospital in Padang and is one of the hospitals with many patient visits. Currently, the drug billing system that is not included in the BPJS patient service package has been implemented using the online pharmacy information system provided by BPJS. However, with this method there are several obstacles, such as (1) having to enter drug data repeatedly (2) requiring a long time in the drug data entry process, (3) and the potential for lost drug claims and losses to the hospital because it is not controlled by an integrated information system. This current work system is considered inefficient, so innovation is needed to create a SIMRS application that has a bridging pharmacy module with the BPJS pharmacy application that can be used by pharmacists in real time, so that the work of drug claims to BPJS is not repeated. With the existence of a pharmacy work module like this, it is hoped that it can improve the efficiency of the pharmacy department's work, speed, accuracy, integration, and efficiency of drug claims to BPJS can be managed well.